Variability of air temperature over a debris-covered glacier in the Nepalese Himalaya - Steiner, Jakob F.; Pellicciotti, Francesca (International Glaciological Society, 2016)
Estimates of melt from debris-covered glaciers require distributed estimates of meteorological variables and air temperature in particular. Meteorological data are scarce for this environment, and spatial variability of temperature over debris is poorly understood. Based on multiple measurements of air and surface temperature from three ablation seasons (2012–14) we investigate the variability of temperature over Lirung Glacier, Nepal, in order to reveal how air temperature is affected by the debris cover and improve ways to extrapolate it. We investigate how much on-glacier temperature deviates from that predicted from a valley lapse rate (LR), analyse on-glacier LRs and test regression models of air temperature and surface temperature. Air temperature over the debris-covered glacier tongue is much higher than what a valley LR would prescribe, so an extrapolation from off-glacier stations is not applicable. An on-glacier LR is clearly defined at night, with strong correlation, but not during the day, when the warming debris disrupts the elevation control. An alternative to derive daytime air temperature is to use a relationship between air and surface temperature, as previously suggested. We find strong variability during daytime that should be accounted for if these regressions are used for temperature extrapolation. ISSN:0260-3055 ISSN:1727-5644